On the behaviour of the White-headed Duck with especial reference to breeding - Matthews, G V T; Evans, Mary E (Wildfowl, 1974)
The first breeding in captivity of the White-headed Duck Oxyura leucocephala at Slimbridge enabled studies to be made of courtship, nesting, incubation and mother/young behaviour. Many undescribed courtship movements are reported. Two females nested in disused Coot Fulica atra nests. Nest building movements were observed in a female which failed to breed and also in a male. Incubation was for 25 days, the females only coming off the nest for short periods during the day. They made excellent mothers. An Oedipus-like display of a duckling to its mother was observed, and adult females occasionally showed male courtship gestures. The males took no part in rearing the young and no definite pair-bond appeared to be established. One duckling was reared to maturity by its mother, and three others artificially. The diving ability of the adults, and its maturation in the ducklings, was examined in detail, over 5,000 dives being timed. There is a brief discussion of taxonomic considerations.